Analysis of Financial Ratio to Stock Price - Ocvika Firda Qurrota'Ayun; Sudarwati Sudarwati; Fithri Setya Marwati (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
Control of Covid-19 has coincided with a period of economic growth in Indonesia. The banking sector felt the effects of this. The purpose of this study is to identify and analyze the effect of Earning Per Share, Debt to Equity Ratio, and Return on Assets on stock prices. For the duration of this research project (2019-2021), we will calculate and analyze the financial ratios of banking companies traded on the Indonesia Stock Exchange relative to their stock prices. Information for this study was gathered, recorded, and analyzed using a documentation strategy. The study's population consisted of 43 businesses, and 17 were randomly selected for sampling by the purposive sampling technique. This study found that while Earning Per Share and Debt to Equity Ratio were both significantly related to stock prices, Return on Assets was not.